Empowerment of Santri in Preventing Acute Respiratory Infections (ARI) through Education on Immune System Resilience and Herbal Processing - Suwito, Bambang Edi; Handayani, Handayani; Agustina, Titin Sholihah; Setiawan, Tirta Akbar Putra; Maula, Elqisha Avatry; Aviciena, Raditya Ahmad; Andriansyah, Ahmad Istan; Firdaus, Farhan Zidany; Azzahra, Aslin Nuroniyah; Imansyah, Atha Zaky; Berliyani, Jella; Rodhiyana, Rosda (Indonesia Berdaya, 2026)
comprehensive education on ARI prevention. The program involved 20 female santri and was implemented through a series of activities, including counseling, practical training in herbal processing, and the initiation of a Family Medicinal Plant (TOGA) garden. Evaluation results show a significant increase in knowledge, proven by an average post-test score increase of 6.5% and a shift in knowledge classification to the "Good" category (from 75% to 95%). Furthermore, the program successfully formed a group of santri cadres responsible for managing the TOGA garden, establishing a model for sustainability. Overall, this program not only successfully increased the individual capacity of the santri but also created a sustainable, community-based support system, which can serve as an important foundation for health improvement in the pesantren environment